Efficacy of Bovine Respiratory Syncytial Virus Vaccines to Reduce Morbidity and Mortality in Calves Within Experimental Infection Models: A Systematic Review and Meta-Analysis - Martinez, David A.; Newcomer, Benjamin; Passler, Thomas; Chamorro, Manuel F. (Frontiers in Veterinary Science, 2022)
Producers and veterinarians commonly use vaccination as the main strategy to reduce the incidence of bovine respiratory syncytial virus (BRSV) infection in calves; however, supportive evidence of BRSV vaccination efficacy has been inconsistent in the literature. The objective of this meta-analysis was to evaluate data from controlled studies on the efficacy of commercially available BRSV vaccines on reducing calf morbidity and mortality after experimental infection with BRSV. A systematic review and meta-analysis was performed in BRSV experimental challenge studies that reported the efficacy of commercially available modified-live virus (MLV) and inactivated BRSV vaccines on protection against calf morbidity and mortality. The studies included in the analysis were randomized, controlled, clinical trials with clear definitions of calf morbidity and mortality. Risk ratios with 95% confidence intervals and forest plots were generated. Fourteen studies including 29 trials were selected for the analysis. Commercially available MLV BRSV vaccines reduced the risk of calf mortality after experimental infection with BRSV. Modified-live virus vaccines reduced the risk of morbidity in calves with absence of serum maternal antibodies at initial vaccination; however, MLV vaccination of calves with maternal immunity did not result in significant morbidity reduction. Vaccination of calves with commercially available MLV BRSV vaccines reduces the risk of mortality after experimental BRSV infection. Although results from experimental challenge studies do not always represent the conditions of natural infection, veterinarians can use this information to make vaccine recommendations in the absence of randomized trials performed under natural occurrence of disease. Modified-live virus vaccines reduced the risk of morbidity in calves with absence of serum maternal antibodies at initial vaccination, but failed to demonstrate significant morbidity reduction when calves were vaccinated in the face of maternal immunity. Results from experimental challenge studies do not always represent the conditions of natural infection and caution should be used when making vaccine recommendations.